Neo-Assyrian Treaties from the Royal Archives of Nineveh - Parpola, Simo
1. The Zakutu Treaty 83-1-18,45 (ABL 1239) + 83-1-18,266. Photo p. 189; 2. Esarhaddon's Accession Treaty 83-1-18,420 + 83-1-18,493 (CT 53, 937) + Bu 91-5-9,131. Copy p. 187; 3. Oath of Loyalty to Esarhaddon Bu 91-5-9,22. Photo p. 188; 4. Treaty with a Vassal King K. 4439 Photo p. 188; 5. The Akitu Treaty VAT 11449 (Ebeling PKTA pl. 31). - 180-183: Excursus: On the term adê, "treaty, covenant".